Academia journal of biology Volume 42, Number 4 (H. Vietnam academy of science and technology, 2020)
Contents:The freshwater copepod genus Mesocyclops (Copepoda, Cyclopoida, Cyclopidae) in Vietnam; Additional records of the genus Acropimpla Townes (Hymenoptera: Ichneumonidae: Pimplinae) from Vietnam and an updated key to species; The DNA barcoding data and genetic distance of leaf beetles (Coleoptera, Chrysomelidae) in Vietnam;....
Formerly Tạp chí sinh học (Journal of Biology)
Keywords: Tạp chí